2003
DOI: 10.1017/s0022112002003063
|View full text |Cite
|
Sign up to set email alerts
|

Numerical experiments on strongly turbulent thermal convection in a slender cylindrical cell

Abstract: Numerical experiments are conducted to study high-Rayleigh-number convective turbulence ($Ra$ ranging from $2\times 10^6$ up to $2\times 10^{11}$) in a $\Gamma=1/2$ aspect-ratio cylindrical cell heated from below and cooled from above and filled with gaseous helium ($Pr=0.7$). The numerical approach allows three-dimensional velocity, vorticity and temperature fields to be analysed. Furthermore, several numerical probes are placed within the fluid volume, permitting point-wise velocity and temperature time seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

51
316
2
11

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 282 publications
(380 citation statements)
references
References 28 publications
51
316
2
11
Order By: Relevance
“…1A. The statistical properties of the flow are consistent with those observed in previous works (19,20), particularly the Nusselt number (which measures the ratio of convective to conductive heat transfer) and the mean temperature and velocity field profiles (Fig. S1).…”
Section: Modelssupporting
confidence: 87%
“…1A. The statistical properties of the flow are consistent with those observed in previous works (19,20), particularly the Nusselt number (which measures the ratio of convective to conductive heat transfer) and the mean temperature and velocity field profiles (Fig. S1).…”
Section: Modelssupporting
confidence: 87%
“…This Ra dependence has two important implications. First, the volume average ratio h f r i V =h m r i V will decrease with increasing Ra, a trend which agrees with the recent numerical results [10] but is opposite to that given by the first scenario of the GL theory [2,5]. Second, the measurements clearly reveal two competing effects of turbulence.…”
supporting
confidence: 82%
“…After all, the convective flow is driven by instabilities of the upper and lower thermal boundary layers. Recent experiment [8] and numerical simulations [9] showed that the ratio of the boundary contribution of T r to the corresponding bulk contribution is an increasing rather than a decreasing function of Ra, as was commonly believed. These studies suggest that the global heat transport measurements will always be ''contaminated'' by contributions from the boundaries.…”
mentioning
confidence: 83%